Dancing to improve balance control, cognitive-motor functions and quality of life after stroke: a study protocol for a randomised controlled trial - Emmanuel Morice; Julien Moncharmont; Clémentine Jenny; Anne-Violette Bruyneel (BMJ Open)
Introduction Dance is an intrinsically motivating activity that includes social interaction, stimulation through music, the pleasure of moving despite pathology-induced motor limitations, and it also has good perceived benefits among participants. Feeling pleasure while moving is essential to finding the motivation to engage in a rehabilitation programme. It is, therefore, urgent to provide persons in a poststroke situation with motivating physical activity opportunities. Very few studies have examined dance in a stroke context, while it is highly adapted and effective for other chronic conditions.Our primary objective is to assess the effects of dance programme on patients’ balance control after stroke. Our secondary objective is to investigate the effects of dance on cognitive function, strength, coordination, functional status, balance confidence, quality of life, motivation and adherence. Our hypothesis is that dance increases balance and motor capacities, and improves poststroke quality of life, adherence and motivation.Methods and analysis Forty-eight subjects with stroke in subacute phase will be randomised into two groups: (1) intervention (dance and standard rehabilitation) and (2) control (standard rehabilitation). Before intervention, stroke severity, cognitive abilities and motor capacities will be assessed. Two baseline tests will be planned to evaluate the stability of individuals. Participants will attend a weekly 60-min dance class for 6 weeks. Cognitive and motor functions (balance, lower-limbs strength, coordination and motor level), quality of life (Stroke-Specific Quality of Life Scale) will be measured at weeks 4 and 6 in both groups. Participant satisfaction with regard to dance will be tested, as well as adherence and adverse effects.Ethics and dissemination Ethics approval has been granted by the Swiss Ethics Committee of the CER Vaud (2019-01467). Outcomes will be disseminated through publication in peer-reviewed journals and presentations at conferences.Trial registration number NCT04120467.